Synthetic cannabinoids use in a sample of opioid-use disorder patients - Alías-Ferri, María; Pellegrini, Manuela; Marchei, Emilia; Pacifici, Roberta; Rotolo, Maria Concetta; Pichini, Simona; Pérez-Mañá, Clara; Papaseit, Esther; Muga, Robert; Fonseca, Francina; Farré, Magi; Torrens, Marta (Frontiers in Psychiatry, 2022)
Cannabis is the most widely consumed illegal drug in the world and with the gain in popularity of synthetic cannabinoids they are increasingly replacing it. These substances are a type of new psychoactive substance that mimics the cannabis effects but often are more severe. Since, people with opioids use disorder use widely cannabis, they are a population vulnerable to use synthetic cannabinoids. In addition, these substances are not detected by the standard test used in the clinical practice and drug-checking is more common in recreational settings. A cross-sectional study with samples of 301 opioid use disorder individuals was carried out at the addiction care services from Barcelona and Badalona. Urinalysis was performed by high-sensitivity gas chromatography-mass spectrometry (GC-MS) and ultra-high-performance liquid chromatography-high –resolution mass spectrometry (UHPLC-HRMS). Any synthetic cannabinoid was detected in the 4.3% of the individuals and in 23% of these samples two or more synthetic cannabinoids were detected. Among the 8 different synthetic cannabinoids detected, most common were JWH-032 and JWH-122. Natural cannabis was detected in the 18.6% of the samples and only in the 0.7% of them THC were identified. Several different synthetic cannabinoids were detected and a non-negligible percentage of natural cannabis was detected among our sample. Our results suggest that the use of synthetic cannabinoids may be related to the avoidance of detection. In the absence of methods for the detection of these substances in clinical practice, there are insufficient data and knowledge making difficult to understand about this phenomenon among opioid use disorder population.